IMPLEMENTASI CASE BASED REASONING UNTUK RESEP MASAKAN TRADISIONAL JAWA (Information Technology and Telematics, 2014)
Abstract With an assortment of traditional Javanese cuisine, people who want to make a dish would be confused to determine the Javanese traditional cuisine menu. Many people who do not understand the Javanese traditional recipes and how to make it, especially if the person only has a few ingredients that he had. This study is an implementation of the Case-Based Reasoning (CBR) based mobile web, with the aim of facilitating the user in finding the Javanese traditional recipes and do not need to be asked directly to the experts. In this study the process of finding a traditional recipe using Java with case based reasoning methods that implement four process steps, namely retrieve, reuse, revise, retain. In the process of looking for similarities between the system retrieve the input material with the material recipes. To retrieve the process will be weighted using the nearest neighbor method. In the process of reuse highest weighting the results to be used as a solution. In the process of revise the results of weighting less than 50 percent of the system will not give advice, but the system will store data in a database for material given by the expert solution. Retain the process used when a solution has been found by the experts and save them back to the database to be used in the search of new cases. To facilitate the process data menu, materials, and revise given the admin side.Keywords : Javanese Traditional Recipes, Case Based Reasoning, Nearest Neighbor.